The Effect of Corporate Social Responsibility (CSR) and Profitability on BRI Syariah Company Value (BRIS) for the 2018-2020 Period - Wahyu Hidayat Febriansyah; Yulistia Andriyani; Nurul Hak; Khairiah Elwardah (Journal of Indonesian Management, 2021)
This study aims to determine whether Corporate Social Responsibility and Profitability affect the company value of Islamic Banks. The samples in this study were BRIS. Corporate Social Responsibility is measured using a checklist based on GRI G4. Meanwhile, profitability is measured by return or assets and firm value is measured by the Tobin's Q ratio. Hypothesis testing uses the Time Series analysis method using the Eviews 8.1 software. The results of this study indicate that: (1) Corporate Social Responsibility variable does not affect the company value of Islamic Banks; and (2) the profitability variable has an effect on the firm value of Islamic Banks.